QTNTR: A New Secure NTRUEncrypt Alternative with a High Level of Security - Huda Abdulateef Ali, Hassan Rashed Yassein (Mathematical Statistician and Engineering Applications, 2022)
Due to its efficiency in resisting attacks, the encryption algorithm, NTRUEncrypt has received a lot of attention. Many researchers have improved the performance of the NTRU cryptosystem. This paper introduces QTNTR, a commutative and associative multidimensional public-key cryptosystem. It is built on quintuple algebra, with one public key and two private keys as the mathematical structure. Also, it has a good resistance against attacks, and its performance is significantly different from that of conventional public-key cryptosystems.